Integrating multi-trait and multi-index approaches for identifying drought tolerant tropical maize genotypes - Azrai, Muhammad; Aqil, Muhammad; Efendi, Roy; Andayani, Nining Nurini; Suwardi,; Zainuddin, Bunyamin; Pabendon, Marcia B.; Sitaresmi, Trias; Anshori, Muhammad Fuad; Riadi, Muhammad; Yasin, Muhammad; Laurenze, Reynaldi; et al. (Frontiers in Sustainable Food Systems, 2025)
Drought stress is a critical constraint to maize production in tropical regions, impairing growth and reducing yield stability. In this study, a panel of hybrids was assessed under both well-watered and drought-stress conditions using yield-based drought tolerance indices and the Multi-Trait Genotype-Ideotype Distance Index (MGIDI). Thirty-three tropical maize hybrids were evaluated under optimal and water-limited conditions across two locations using a randomized complete block design. Drought stress was imposed 40 days after planting until the milk stage following CIMMYT protocols, and data on morphological, physiological, and yield traits were recorded. The dataset was subjected to multivariate analyses, including Principal Component Analysis and hierarchical clustering, as well as four yield-based drought tolerance indices: Stress Tolerance Index (STI), Stress Susceptibility Index (SSI), Yield Stability Index (YSI), and Harmonic Mean Index (HI). Yield-based drought indices identified six superior hybrids (GE13, GE17, GE21, GE26, GE29, and GE32) characterized by high yield stability and minimal reductions under stress. Multi trait analysis using the MGIDI, which integrated various morpho-physiological traits further highlighted GE13, GE21, and GE32 as consistently close to the ideotype. The overlap between yield-based indices and MGIDI confirms the robustness of these three hybrids, while demonstrating the value of integrating complementary selection tools for precise identification of drought tolerant genotypes.